Carbon markets and emission derivatives: The pricing of derivatives in the EU ETS - Costa, João de Andrade Dias da (2014)
The European Union’s Emissions Trading Scheme (EU ETS) is the world’s largest carbon market operating and an important piece for European environmental policy. Launched in 2005, this market-scheme trades allowances and derivatives’ contracts that represent the right to emit a certain amount of pollutant gases. This work intends to understand the role of carbon markets in general, and the pricing of derivatives’ contracts traded in the EU ETS. It was taken as basis the Black-Scholes (1973) model and its further extensions by Merton (1973) and Merton (1976), applying then a model suggested by Daskalakis, Psychoyios and Markellos (2009) to value a call option written on emission allowances. The numerical results suggest that time to maturity and the moneyness degree had influence in the options’ price, while the jump intensity did not have an influence in the obtained results Based on the application of the model, it was then derived, using the put-call parity, the value of a put option under the same basic features. It was also conducted a sensitivity analysis to the call option, in which it was concluded that, under the model specifications, volatility shows a strong influence within the studied call options’ value.